Efficiency and Quantitative Structure-Activity Relationship of Monoaromatics Oxidation by Quinone-Activated Persulfate - Shi, Jiaqi; Long, Tao; Zhou, Yuxuan; Wang, Lei; Jiang, Cuiping; Pan, Dongguo; Zhu, Xin (Frontiers in Chemistry, 2021)
Quinones and quinone-containing organics have potential of activating persulfate to produce sulfate radical. In this work, the optimal condition for quinone activation of persulfate was investigated. It was found representative monoaromatics were degraded fastest in alkaline environment (pH 10.0), but excessive alkalinity restrained the reaction instead. The mechanisms to explain this phenomenon were speculated. The effect of initial quinone concentration on persulfate oxidation was also investigated at pH 10.0. In addition, a quantitative structure-activity relationship model was established with 15 kinds of monoaromatics, which revealed the most negative atomic net charges on carbon atom played an important role on degradation rates. Chemicals with a smaller qC- were easier oxidized in quinone-activate system. This finding helps further exploration of effective activator in alkaline environment.